Efektivitas Project Based Learning Terhadap Digital Literacy Skill Mahasiswa Pascasarjana Teknologi Pendidikan Pada Mata Kuliah Analisis Jurnal Ilmiah Di Universitas Negeri Surabaya - Azmi, Nurul; Arianto, Fajar; Maureen, Irena Y. (Jurnal Ilmiah Mandala Education (JIME), 2022)
This research aims to test the effectiveness of project-based learning on digital literacy skills of graduate students of educational technology in scientific journal analysis courses at State University of Surabaya. This research uses a quantitative approach, in research using the Pre-Experimental Design method because it has not fully conducted experiments. This research was only conducted in experimental classes without any control class as a comparison. Based on reference to the theory found to find out the implementation of project-based learning in support of this research, observation assessment instruments are used to determine the implementation of digital literacy in lecture activities. To obtain data on digital literacy capabilities used digital literacy capability assessment instruments that have been developed before and adapted to research needs based on existing theories.Based on the results of the study, it was obtained that the project-based learning model significantly affects students' digital literacy skills.  In this case, it can be concluded that the research objectives have been achieved by knowing the effectiveness of project-based learning on digital literacy skills of graduate students of Educational Technology in scientific journal analysis courses at State University of Surabaya.